Association between life’s essential 8 and hyperuricemia among adults in the United States: insights from NHANES 2005–2018 - Wang, Xiaolan; Fan, Jingxiu (Frontiers in Medicine, 2024)
Background: Hyperuricemia is a significant risk factor for various metabolic and cardiovascular conditions. Life’s Essential 8 (LE8), a comprehensive measure of cardiovascular health promoted by the American Heart Association, may have a protective role against hyperuricemia. This study aims to evaluate the association between LE8 scores and hyperuricemia in a representative sample of US adults. Methods: We conducted a cross-sectional study using data from the National Health and Nutrition Examination Survey (NHANES) 2005–2018, encompassing 26,885 adults. LE8 scores were calculated based on diet, physical activity, nicotine exposure, sleep health, body mass index, blood lipids, blood glucose, and blood pressure. Hyperuricemia was defined as serum uric acid levels ≥7.0 mg/dL in men and ≥6.0 mg/dL in women. Logistic regression and generalized additive models (GAMs) were used to analyze the relationship between LE8 scores and hyperuricemia, adjusting for potential confounders. Results: Higher LE8 scores were significantly associated with lower odds of hyperuricemia (OR per 10-point increase: 0.73, 95% CI: 0.72-0.75, P < 0.001). Stratified analyses revealed consistent protective effects across subgroups defined by sex, age, race/ethnicity, PIR (poverty income ratio), education level, drinking status, eGFR, and CVD status. Logistic regression and GAM analyses both confirmed a linear relationship between increasing LE8 scores and reduced hyperuricemia risk. For example, in males, the OR was 0.81 (95% CI: 0.78-0.84), and in females, it was 0.66 (95% CI: 0.64-0.68). Conclusion: The findings suggest that higher LE8 scores are robustly associated with lower odds of hyperuricemia in US adults. These results support the promotion of comprehensive cardiovascular health behaviors encapsulated by LE8 to mitigate hyperuricemia risk. Further studies are needed to explore the causal pathways and potential interventions.